The External Wealth of Nations : Measures of Foreign Assets and Liabilities for Industrial and Developing Countries - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 1999)
Capital flows are closely monitored, but surprisingly little is known about the stocks of external assets and liabilities held by countries, especially in the developing world. This paper constructs estimates of foreign assets and liabilities and their equity and debt subcomponents for 66 industrial and developing countries for the period 1970-97. It explores the sensitivity of estimates of stock positions to the treatment of valuation effects not captured in balance of payments data. Finally, it characterizes the stylized facts of estimated stocks and asks whether there are trends in net foreign asset positions and differences in debt-equity ratios across countries.